Storage protein profile and amino acid content in wild rice Oryza glumaepatula - Santos, Karina Freire D’eça Nogueira; Silveira, Ricardo Diógenes Dias; Martin-Didonet, Claudia Cristina Garcia; Brondani, Claudio (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to determine the total protein profile and the contents of the four major protein fractions (albumin, globulin, prolamin and glutelin) and of the amino acids in the endosperm of the rice wild species Oryza glumaepatula. The experiment was performed with 29 accessions of this species, collected from 13 Brazilian locations, and two commercial cultivars. Protein samples were prepared using dried, polished, and ground grains to obtain homogeneous, dry flour used in the preparation of extracts. Oryza glumaepatula accessions were identified with the highest levels of total protein, albumin and glutelin protein fractions, and amino acids (with the exception of tryptophan) in comparison to the two analized rice cultivars. The albumin and glutelin profiles in SDS-Page were distinct between rice cultivars and O. glumaepatula. This wild species has the potential to increase the nutritional quality of rice storage protein through interspecific crosses.